Development of canned "Adobo" product from cull chicken meat (Gallus gallus domesticus Linn) - Cabrera, Cleofe D.
Cull chicken meat (CCM) was utilized as the primary raw material in the production of a good quality, low-cost and nutritious canned chicken adobo product. The development of the new product involved standardization of formulation and procedure which resulted in an optimum meat combination of 30:70 pork to CCM. Processing for 30 minutes rendered the product commercially sterile. Pre-cooking the product for five minutes was also found to give the product the desired firm but tender texture. The standard formulation, procedure and thermal process developed were tested on a bench scale production showing repeatability of the process. Cost analysis showed that a can of the product weighing 210±10 grams can be sold at a practice of P37.81. Consumer acceptability test on the product revealed that the consumers found the product to be of very good quality and with an acceptability score which corresponded to a description of like very much.